Simulated vaccine efficacy trials to estimate HIV incidence for actual vaccine clinical trials in key populations in Uganda. Issue 15 (3rd April 2019) - Abaasa, Andrew; Nash, Stephen; Mayanja, Yunia; Price, Matt; Fast, Patricia E.; Kamali, Anatoli; Kaleebu, Pontiano; Todd, Jim
Highlights: New HIV infections continue to occur amidst available HIV prevention interventions. Poor adherence is indicated, therefore an affordable HIV vaccine is urgently needed. HIV vaccine efficacy trials need accurate estimate of incidence in the control arm. Designs using comparison to 'observational data as control arms' are contemplated. We show some of the pitfalls that may arise with comparison to observational control. Abstract: Background: Fisherfolks (FF) and female sex workers (FSW) in Uganda could be suitable key populations for HIV vaccine efficacy trials because of the high HIV incidence and good retention in observational cohorts. However, the observed HIV incidence may differ in participants who enroll into a trial. We used simulated vaccine efficacy trials (SiVET) nested within observational cohorts in these populations to evaluate this difference. Methods: SiVETs were nested in two observational cohorts (Jul 2012–Apr 2014 in FF and Aug 2014–Apr 2017 in FSW). From Jan 2012 all observational cohort participants (aged 18–49 years) presenting for quarterly visits were screened for enrolment into SiVETs, until 572 were enrolled. Those not enrolled (screened-out or not screened) in SiVET continued participation in the observational cohorts. In addition to procedures in the observational cohorts (HIV testing & risk assessment), SiVET participants were given a licensed Hepatitis B vaccine mimicking a schedule of a possible HIV vaccine, and followed-up for 12 months. Findings: In total, 3989 participants were enrolled into observational cohorts (1575 FF prior to Jul 2012 and 2414 FSW prior to Aug 2014). Of these 3622 (90.8%) returned at least once, 672 (44.1%) were screened and 572 enrolled in the SiVETs. HIV incidence pre SIVETs was 4.5/100 person years-at-risk (pyar), 95%CI (3.8–5.5). HIV incidence in SiVET was 3.5/100 pyar, (2.2–5.6) and higher in those not enrolled in the SiVET, 5.9/100 pyar, (4.3–8.1). This difference was greatest among FF. In the 12 months post-SIVET period (FF, May 2014–Apr 2015 and FSW, May 2017–Apr 2018), the HIV incidence was 3.7/100 pyar, (2.5–5.8). Interpretation: HIV incidence was lower in SiVET participants compared to non-SiVET. This difference was different for the two populations. Researchers designing HIV efficacy trials using observational cohort data need to consider the potential for lower than expected HIV incidence following screening and enrolment.